2012
DOI: 10.1111/j.1540-4609.2011.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Textbooks and Students’ Learning Experiences

Abstract: The contribution of the e-textbooks can be enormous considering their additional supporting features, but adoption has not crystallized yet. This study examines the relevant experiences of college students in terms of how the use of e-textbooks may enhance their learning. A survey study was conducted to measure the perceptions of each student on how helpful an e-textbook is for facilitating learning (i.e., E-book Helpfulness), how well it promotes his/her involvement in learning (i.e., Student Involvement), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 20 publications
4
51
0
6
Order By: Relevance
“…Within the Information Systems domain, scholars [14,15,16,17,18] predominantly applied causal models extending the Technology Acceptance Model (TAM). For example, Lai and Ulhas [15] and Lai and Chang [14] had similar findings in that perceived usefulness, convenience, perceived enjoyment, compatibility and media richness contributed to e-book acceptance.…”
Section: Related E-book Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Within the Information Systems domain, scholars [14,15,16,17,18] predominantly applied causal models extending the Technology Acceptance Model (TAM). For example, Lai and Ulhas [15] and Lai and Chang [14] had similar findings in that perceived usefulness, convenience, perceived enjoyment, compatibility and media richness contributed to e-book acceptance.…”
Section: Related E-book Literaturementioning
confidence: 99%
“…Their qualitative findings suggested that e-reader adoption may not involve a binary choice between print and e-formats. Interestingly, Sun, Flores and Tanguma [18] found that etextbooks enhanced student learning and that this outcome was mediated by students' involvement in the use of e-books in the classroom. For students with disabilities such as vision impairment and dyslexia, e-textbooks offered potential improved access.…”
Section: Related E-book Literaturementioning
confidence: 99%
“…Many previous studies have demonstrated students' usage of e-textbook (Daniel, & Woody, 2013;McGowan et al 2009;McFall et al 2006;Nicholas et al 2010;Quan-Haase & Martin, 2011;Rose, 2011;Rockinson-Szapkiw et al, 2013;Sun et al 2012;Weisberg 2011). For example, McFall et al explored university teachers' usage of e-textbooks in reading courses and reported positive responses from teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a wealth of international literature that supports the fact that the majority of students today still prefer to use print books rather than e-books in an academic setting (Wu & Chen 2011;Sun, Flores & Tanguma 2012;Muir & Hawes 2013;Cassidy, Martinez & Shen 2012;Gregory 2008;Elias, Phillips & Luechtefeld 2012;Abdullah & Gibb 2008). Some students have clearly indicated that they prefer using print books, because they perceive e-books as hard to navigate, despite the 'anywhere-and-anytime' access that e-books supposedly offer (Gregory 2008: 267).…”
Section: The E-textbook Dilemmamentioning
confidence: 99%
“…Some research has been done about e-books in an academic setting (Gregory 2008;Folb, Wessels & Czechowski 2011;Nicholas & Lewis 2008;Shin 2011;Sun, Flores & Tanguma 2012) but several unanswered questions still remain, especially in the South African context. For example, why is the uptake of e-books, and specifically e-textbooks, so slow?…”
Section: Introductionmentioning
confidence: 99%